(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
Migration is a constant companion of civilization. Human communities have been migrating throughout the lands. There are various reasons and the different conditions that drive the people to migrate individually or in groups from one to another place, on a permanent or temporary basis. Bosnia and Herzegovina has been characterized through its history by economic emigration and immigration, but also in the past seven centuries there exist a record of several waves of forced – internal and external – migration. Past thirty years have been particularly marked by the war against Bosnia and Herzegovina that demographically devastated the country, all its people, their families and territories. The demographic emptying of Bosnia and Herzegovina continued in the post-war period, and has been amplified in the past few years. The recent surge in emigration is caused by security, economic and other dilemmas produced by political conflicts, threatening to aggravate, and being transformed into fear of a renewed armed conflict, fear of poverty, a fear of legal uncertainty, corruption.